Peningkatan Pemahaman Siswa Pada Pelajaran Bahasa Indonesia Materi Teks Informasi Kelas 6 SDN Betoyoguci Kecamatan Manyar Kabupaten Gresik Melalui Penggunaan Symbolc Model - S, Saiffudin; Rahmawati, Endah (JURNAL WAHANA PENDIDIKAN DASAR, 2016)
The problems raised in this research is: Is there an increase in learning Indonesian education through a strategy of symbolic model? Observation of this research is done directly at the time of Indonesian Language Learning in grade 6 SDN Betoyoguci District of Manyar Gresik on competencies standards provide information and a verbal response that is associated with the basic competencies Convey the message or information obtain from a variety of  media with materials that coherent, well, and right. This research was carried out for two months, starting in September 2015 until October 2015, through three cycles. In general, the study cycle through the steps of planning, implementation, observation, and reflection activities. The conclusion of the research note students learning outcome of grade 6 SDN Betoyoguci District of Manyar Gresik to the basic competence Convey the message or information obtain from a variety of  media with materials that coherent, well, and was able to experience a significant increase after implementation of learning activities through a strategy Symbolic model.